The dynamics of the profitability and growth of restaurants: The case of Norway - Leiv Opstad; Johannes Idsø; Robin Valenta (Economies, 2022)
The restaurant industry is quite similar across borders. It is a labour-intensive industry that is important for tourism and employment. It consists mainly of many small businesses that are regionally dispersed. There are many studies that have analysed this sector. However, rather few articles have focused on the dynamics of growth and profit. The purpose of this paper is to apply the theory of profit persistence and the law of proportionate effect (LPE) to Norwegian restaurants by using publicly available public panel data from 2010 to 2019. The sample includes 866 restaurants. One important finding is that Gibrat's law (LPE) does not seem to hold, meaning the growth is not independent of the size of the firms. Small businesses grow faster than the others, and they are also more profitable. There is some degree of profit persistence in the restaurant industry. Profitability is negatively linked to debt ratios but positively related to working capital. The study shows there is a trade-off between size and profit. These findings are useful for the industry and for others (public planning, lenders, and more).
Keywords: 330; Gibrat's law; GMM estimator; law of proportionate effect (LPE); Norway; panel data; profit persistence; restaurant industry